Estimation of the benchmark duration of alternating shift work associated with increased total cholesterol levels among male Japanese workers - Yasushi Suwazono; Mirei Uetani; Mitsuhiro Oishi; Kumihiko Tanaka; Hideki Morimoto; Satoru Nakada; Kouichi Sakata (Nordic Association of Occupational Safety and Health (NOROSH), 2010)
OBJECTIVE: The aim of this study was to estimate the benchmark doses (BMD) and their 95% lower confidence limits (BMDL) for the threshold number of years of alternating shift work associated with a relative increase in serum total cholesterol level (T-Cho), as an index of lipid metabolism. METHODS: We conducted a 14-year prospective cohort study among male workers (N=6886) at a Japanese steel company who had received annual health check-ups between 1991 and 2005. The endpoints were either a 20, 25, 30, 35, 40 or 45% increase in T-Cho levels during the observation period, compared to T-Cho at baseline. We investigated the associations between the years of alternating shift work and the relative increases in T-Cho using pooled logistic regression, adjusted for other potential covariates. RESULTS: We estimated the BMDL and BMD for years of alternating shift work among 40-, 50-, or >50-year old subjects using benchmark responses (BMR) of 5 or 10% and parameters for the duration of alternating shift work and other covariates. Assuming a mean age of 44 years among workers in their 40s, the BMDL/BMD for years of alternating shift work with a BMR of 5% were 21.0/28.0 (≥20%), 21.3/26.1 (≥25%), 24.1/28.8 (≥30%), 25.6/29.8 (≥35%), 27.1/31.5 (≥40%), and 27.7/32.1 (≥45%). CONCLUSIONS: The threshold number of years of alternating shift work that caused a 5% increase in T-Cho was shown to be ≥21 years among middle-aged workers. Special attention should be paid to influence the process at an earlier stage and not when the risk has already materialized.